2019
DOI: 10.1186/s13018-019-1174-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective 5-year study with 96 short curved Fitmore™ hip stems shows a high incidence of cortical hypertrophy with no clinical relevance

Abstract: Background An increased occurrence of cortical hypertrophy (CH) was observed 1–2 years after implanting short curved Fitmore hip stems. There are no published data about either the clinical relevance or the progression of CH over the long term. Methods Ninety-six primary total hip arthroplasties were performed between 2008 and 2010 using the Fitmore hip stem. Clinical and radiological parameters were recorded preoperatively and at 1, 2, 3, and 5 year follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
2
12
1
Order By: Relevance
“…The examined short stem demonstrated almost 50% of the overall subsidence within the first 3 months and then slowed down markedly. However, there was some subsidence up to the last follow-up, which is in accordance with recent findings of Schaer et al [34], who studied the Optimys short stem (Mathys, Bettlach, Switzerland), and Thalmann et al [14], who studied the Fitmore short stem (Zimmer Inc., Warsaw, IN, USA). In contrast, most previously published data on cementless short stems found stabilization of subsidence during a shorter follow-up of 3 months [21,22], 6 months [20], 12 months [19], or 24 months [15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The examined short stem demonstrated almost 50% of the overall subsidence within the first 3 months and then slowed down markedly. However, there was some subsidence up to the last follow-up, which is in accordance with recent findings of Schaer et al [34], who studied the Optimys short stem (Mathys, Bettlach, Switzerland), and Thalmann et al [14], who studied the Fitmore short stem (Zimmer Inc., Warsaw, IN, USA). In contrast, most previously published data on cementless short stems found stabilization of subsidence during a shorter follow-up of 3 months [21,22], 6 months [20], 12 months [19], or 24 months [15].…”
Section: Discussionsupporting
confidence: 89%
“…Various studies have reported on the subsidence of cementless hip stems, with some suggesting an inferior performance of short stem designs compared to conventional stems [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. This could be detrimental for implant survivorship, as several authors suggested a correlation of early stem subsidence with aseptic loosening [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The examined short stem demonstrated almost 50% of the overall subsidence within the rst 3 months and then slowed down markedly. However, there was some subsidence up to the last follow-up, which is in accordance with recent ndings of Schaer et al (34), who studied the Optimys short stem (Mathys, Bettlach, Switzerland) and Thalmann et al (14) who studied the Fitmore short stem (Zimmer Inc., Warsaw, Indiana, USA (17).…”
Section: Discussionsupporting
confidence: 87%
“…Although these implants demonstrated good short-to mid-term outcomes (7,8), there are concerns whether all short cementless proximally-xed femoral stems are able to achieve an adequate primary stem xation and stability. Various studies have reported on the subsidence of cementless hip stems, with some suggesting an inferior performance of short stem designs compared to conventional stems (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). This could be detrimental for implant survivorship, as several authors suggested a correlation of early stem subsidence with aseptic loosening (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the stem of thicker group in the present study, Maier et al reported that radiolucent lines were confirmed at 11% each in Gruen zones 1 and 7 (proximal), 2% in zone 2 and 3% in zone 6 (middle), and 2% in zone 3 and 9% in zone 5 (distal) during a follow-up of ≥ 2 years [ 13 ]. Thalmann et al reported that radiolucent lines were confirmed at 51% in the anteroposterior image and 35% in the axial image in all zones other than the Gruen zone 2 during the first year, which decreased to 20% in the anteroposterior image and 9% in the axial image 5 years later [ 14 ]. In the present study, “proximal and distal” was the most common pattern of radiolucent lines for the thicker group (35.9% before matching and 40% after matching).…”
Section: Discussionmentioning
confidence: 99%